Perancangan Sistem Informasi Persediaan dan Penjualan Sparepart Motor pada Toko Autoshop Berbasis Website - Ruslin Hamid; Saliz Nizar Qomaruzaman; Putri Maulidatur Riskiah; Santi Nurindah (Jurnal Sistem Informasi dan Teknologi Informasi, 2022)
The purpose of this study is to design a website for information systems for inventory and sales of goods at an online motorcycle spare parts store called autoshop. The method used by the researcher is a method that develops information systems with a systematic flow, the steps that are passed one by one starting from the analysis stage to the trial and maintenance stage, system design using the PHP programming language and MySQL database. Website-based sales promotion media for motorcycle parts uses the development of information technology that is needed because it can find extensive information on automotive goods. Results Based on research that automotive goods through the website can provide information in the form of product sales data, customer data, and purchase data reports. The results of the design are carried out to create an information system in the form of inventory and sales of motorcycle parts including the design of an information system using the PHP programming language, namely the CRUD process. The purpose of making this information system is to provide convenience in getting the desired goods, and to make a practical buying and selling transaction system, this also helps revive the community's economy and can meet the needs of automotive goods for those who need these goods.